(untitled) (College of Basic Education Research Journal, 2026)
This research investigates the issue of narcotics as one of the most critical challenges confronting contemporary societies, with a particular focus on Iraq. The study aims to establish the foundational jurisprudential rulings (Ahkam) concerning narcotics by examining scriptural sources and universal Islamic legal maxims. It clarifies the rationale for their prohibition, which is rooted in the preservation of the essential objectives of Sharia (Maqasid al-Sharia), primarily the preservation of life and intellect. To achieve this, the research adopts a descriptive-analytical methodology. It extends beyond merely presenting jurisprudential rulings to analyze the devastating social and health impacts of drug abuse and trafficking, such as increased crime, family disintegration, and the deterioration of public health. The study seeks to highlight the significant intersection between the Islamic perspective on combating narcotics and the United Nations’ Sustainable Development Goals (SDGs), specifically Goal 3 (Good Health and Well-being) and Goal 16 (Peace, Justice, and Strong Institutions). The research concludes that the Islamic legal stance on narcotics is not an abstract religious injunction but rather an integrated preventative and remedial framework aimed at building a safe and sustainable society. In this context, the study presents a forward-looking vision for the role of higher education institutions in Iraq. It calls for the adoption of innovative research and educational strategies, and for leveraging the transformations of Artificial Intelligence (AI) to design effective awareness programs that protect youth and support national efforts to combat this scourge.